2022
DOI: 10.1021/acs.energyfuels.2c00300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvents on Persistent Free Radical Content in the Absence of Reactions

Abstract: The impact of a solvent environment on persistent free radical concentrations at ambient conditions was studied by electron spin resonance spectrometry. The analyte selected was Canadian oil-sand-derived bitumen due to its high persistent free radical content. The ability of 54 different solvents to produce a homogeneous 5 wt % solution of bitumen was evaluated. The influence of solvents on the free radical content in bitumen was determined exclusively for solvents that were capable of quantitatively dissolvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…This finding suggests that the fouling phenomenon being quite complex is controlled not only by the residual oil colloidal stability, which is affected by the asphaltene content, 46 but also by other factors like, for example, the content of free radicals in the asphaltene fraction. 48 50 The increase of the catalyst addition rates contributes to the enhancement of the available catalyst active sites, which with the participation of the hydrogen may saturate the VTB free radicals. It is understandable that this hypothesis needs to be proven by measurement of the free radical content in the hydrocracked vacuum residue, obtained at different catalyst addition rates, and this can be a subject of another study.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that the fouling phenomenon being quite complex is controlled not only by the residual oil colloidal stability, which is affected by the asphaltene content, 46 but also by other factors like, for example, the content of free radicals in the asphaltene fraction. 48 50 The increase of the catalyst addition rates contributes to the enhancement of the available catalyst active sites, which with the participation of the hydrogen may saturate the VTB free radicals. It is understandable that this hypothesis needs to be proven by measurement of the free radical content in the hydrocracked vacuum residue, obtained at different catalyst addition rates, and this can be a subject of another study.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Tannous et al [30], it was also found that at the same level of petroleum dilution the type of solvent affected the free radical concentration. However, this study did not find a relationship between the free radical concentration in the solution with the dipole moment of the solvent.…”
Section: Impact Of Bulk Liquid Compositionmentioning
confidence: 93%
“…Additionally, bulk properties of the solvent such as molecular weight, refractive index, density, and viscosity were not correlated to the free radical concentration of the analyte. Table 3 [30] illustrates the effect of the type of solvent on the persistent free radical concentration. The measurements were all performed at the same concentration of bitumen.…”
Section: Impact Of Bulk Liquid Compositionmentioning
confidence: 99%
“…This indicates most of the asphaltenes would be aromatics having side chains and would contain naphthenic‐aromatic rings. It contains persistent free radicals [19] and is being considered the most reactive part of the bitumen. Figure 4 shows the typical free radical contents of the heavier petroleum fractions.…”
Section: Petroleum and Its Fractionsmentioning
confidence: 99%